2016 IEEE MTT-S International Microwave Symposium (IMS) 2016
DOI: 10.1109/mwsym.2016.7540087
|View full text |Cite
|
Sign up to set email alerts
|

500-750 GHz submillimeter-wave MEMS waveguide switch

Abstract: -This paper presents a 500-750 GHz waveguide based single-pole single-throw (SPST) switch achieving a 40% bandwidth. It is the first ever RF MEMS switch reported to be operating above 220 GHz. The switch is based on a MEMSreconfigurable surface which can block the wave propagation in the waveguide by short-circuiting the electrical field lines of the TE10 mode. The switch is designed for optimized isolation in the blocking state and for optimized insertion loss in the nonblocking state. The measurement results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…An alternative approach utilizes a reconfigurable surface placed in the cross section of the waveguide [2]. At W-band this device showed low losses of 0.65 dB, but scaling to higher frequencies the presence of the comb in the waveguide could incur significant insertion loss and degrade the return loss of the switch [3].…”
Section: R F Microelectromechanical Systems (Rf-mems) Devicesmentioning
confidence: 99%
“…An alternative approach utilizes a reconfigurable surface placed in the cross section of the waveguide [2]. At W-band this device showed low losses of 0.65 dB, but scaling to higher frequencies the presence of the comb in the waveguide could incur significant insertion loss and degrade the return loss of the switch [3].…”
Section: R F Microelectromechanical Systems (Rf-mems) Devicesmentioning
confidence: 99%
“…To the best knowledge of the authors, the RF MEMS switch reported here is the first RF MEMS switch above 220 GHz [21] and the first MEMS waveguide switch above 75 GHz. Very recently, another MEMS waveguide switch operating between 500 to 750 GHz based on a ridge waveguide using an electrostatic actuator was reported [22] and our conference publication [20] was referenced as the first MEMS waveguide switch at these frequencies by that paper.…”
Section: Introductionmentioning
confidence: 99%
“…This MEMS reconfigurable surface waveguide switch concept is very broadband, as the bandwidth is only limited by the waveguide-modes cutoff. The authors have reported, in a recent conference publication [20], the basic concept of this MEMS waveguide switch at WM-380 (WR-1.5) frequencies. This paper is an extension of the conference publication and discusses the switch design in detail and present new measurement data (both electromechanical and RF).…”
Section: Introductionmentioning
confidence: 99%
“…RF-MEMS has been utilized in mass-market products for several years, with smartphones being among the foremost adopters [8]. Beyond this conventional application, the remarkable RF performance of RF-MEMS, coupled with its substantial reconfigurability and design flexibility, as well as relatively low manufacturing costs, positions it as a compelling Key Enabling Technology (KET) for advancing mobile communication beyond the 5th generation (B5G), into 6G and Future Networks (FN), particularly targeting operation in the sub-THz range (100-300 GHz) and beyond [9][10][11][12][13]. A pivotal phase in the development of innovative RF-MEMS devices involves modeling, as optimizing their characteristics entails navigating a plethora of Degrees of Freedom (DoF), encompassing both technological and geometrical aspects.…”
Section: Introductionmentioning
confidence: 99%